On the Relation Between Over-Indebtedness and Well-Being - Ferreira, Mário B. (2021)
Ferreira, M. B., de Almeida, F., Soro, J. C., Herter, M. M., Pinto, D. C., & Silva, C. S. (2021). On the Relation Between Over-Indebtedness and Well-Being: An Analysis of the Mechanisms Influencing Health, Sleep, Life Satisfaction, and Emotional Well-Being. Frontiers in Psychology, 12, 1-14. [591875]. https://doi.org/10.3389/fpsyg.2021.591875